2017
DOI: 10.1016/j.chest.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Asymptomatic Presentation Status in Patients With Paroxysmal and Sustained Atrial Fibrillation

Abstract: UMIN Clinical Trials Registry; No.: UMIN000005834; URL: www.umin.ac.jp/ctr/index.htm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…5,13 Therefore, assuming that silent paroxysmal AF is generally associated with frequent AF episodes, once again, the "transitional form" theory is likely. The present study and a previous one 2, 3 showed an association of silent paroxysmal AF with a previous stroke. The most likely interpretation is that asymptomatic patients with a previous stroke were more Note: The values are the mean ± SD, the n (%).…”
Section: Silent Paroxysmal Af's Higher Likelihood Of Atrial Arrhythsupporting
confidence: 83%
See 4 more Smart Citations
“…5,13 Therefore, assuming that silent paroxysmal AF is generally associated with frequent AF episodes, once again, the "transitional form" theory is likely. The present study and a previous one 2, 3 showed an association of silent paroxysmal AF with a previous stroke. The most likely interpretation is that asymptomatic patients with a previous stroke were more Note: The values are the mean ± SD, the n (%).…”
Section: Silent Paroxysmal Af's Higher Likelihood Of Atrial Arrhythsupporting
confidence: 83%
“…Recent clinical trials have suggested silent paroxysmal AF as a possible cause of cryptogenic strokes . Moreover, higher mortality in patients with silent vs symptomatic paroxysmal AF has recently been reported . There is thus an urgent need for a comprehensive approach for early diagnosis of silent paroxysmal AF.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations